Menopause as a cardiovascular risk factor: therapeutic implications of hypertension - Posadzy-Małaczyńska, Anna (Menopause Review/Przegląd Menopauzalny, 2011)
Oestrogen deficiency after the cessation of the ovarian function in women causes many subjective ailments as well as serious health problems. In Poland, similarly to other developed countries, cardiovascular diseases are the main cause of death in women after 50 years of age. Menopause not only induces an increase of blood pressure, but is also an independent risk factor of cardiovascular complications, especially strokes when hypertension coexists. The analysis of patients after 64 years of age revealed the prevalence of hypertension in 81% of women and 66% of men. Hypertension is one of the most important risk factors of coronary artery disease; in hypertensive women, the risk of development of different cardiovascular complications is 4 times higher than in coeval men. Menopause provokes also increased development of atherosclerosis. Cardiovascular risk factors become more often assessed as the elements of the metabolic syndrome. Some of previous clinical trials undermined the positive influence of the treatment of mild hypertension in women because of a lower relative risk in this group. The INDANA analysis showed a great absolute benefit of treatment of hypertension in older women as well as in black people in comparison to men. The decision concerning therapy in younger women, especially in Caucasians, has to be made individually depending on the level of the cardiovascular risk. Diuretics are preferably used in treatment of hypertensive women because of their additional advantage; they have a positive impact on calcium balance that is impaired during menopause. On the other hand, usage of renin-angiotensin-aldosterone system blockers results from the patomechanism of hypertension at the menopausal age and their advantages are revealed in clinical trials.